(untitled) (Al-Qamar, 2024)
In the aftermath of the US withdrawal from Afghanistan, a sense of resentment among the people of Afghanistan toward Pakistan has been observed. The Afghans have displayed their resentment towards Pakistan mainly through public protests and online social media campaigns. For Islamabad, this display of antipathy by the Afghans may be rather difficult to comprehend since Islamabad has been hosting millions of Afghan refugees for over three decades. Against this backdrop, this research paper delves into the historical undercurrents of Afghan resentment towards Pakistan and discovers the causes behind it. In doing so, this research paper explores the nature of Pakistan’s foreign policy towards Kabul and its role in shaping Afghan perceptions. This paper highlights factors such as Pak-Afghan historical grievances, perceived interference in the internal affairs of Afghanistan, and a protracted refugee crisis as the main drivers of Afghans’ resentment toward Pakistan. Lastly, this paper has sought to put forward offers some potential pathways that can be adopted so as to address the rising anti-Pakistan sentiment and promote constructive engagement between Pakistan and Afghanistan.